Ethical Challenges And Modifications In Research Methodology Related To Pediatrics - Mishra, Jyoti; Verma, Mithilesh (International Research Journal of Ayurveda & Yoga, 2020)
Pediatric subjects are included in vulnerable population and according to ICMR ( Indian Council for Medical Research) they also have equal right to be included in research so that benefits occurring from the research can apply to them as well. There are some ethical issues which arise during research conducting on such population like availability and access, vulnerability to harm or damage, informed consent, confidentiality, exploitation, compensation etc. The researcher must take care of these all ethical issues while involving such subjects in the researches. ICMR has laid down some guidelines for research on such type of subjects like these population should be included in the research only when the research is directly answering the health needs or requirement of the group. Further benefits of the research should out weight the risk to the population. The Ethical Committee should determine the vulnerability and ensure that additional safeguard and continuous monitoring mechanisms are established. It is also mandatory for the researcher to be well trained and competent in his work to maintain safety.